2022
DOI: 10.1186/s12888-022-04094-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinically assessed and perceived unmet mental health needs, health care use and barriers to care for mental health problems in a Belgian general population sample

Abstract: Background Mental health problems often remain undetected and untreated. Prior research suggests that this is mainly due to a lack of need-perception and attitudinal barriers. The aim of this study is to examine unmet mental health needs using both a clinically assessed and a self-perceived approach in a Belgian province. Methods A cross-sectional survey study with a weighted representative sample of 1208 individuals aged 15 – 80 years old was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…This leads to an estimated population prevalence of 3.6% perceived partially or fully unmet mental health needs among suicide ideators. As a reference, this number is 14% in the total sample (i.e., both with and without suicidal ideation), as one in ten people perceives a fully unmet mental health need and 4% perceives a partially unmet need [ 50 ]. Thus, those reporting suicidal ideation account for about one-quarter of all perceived unmet needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to an estimated population prevalence of 3.6% perceived partially or fully unmet mental health needs among suicide ideators. As a reference, this number is 14% in the total sample (i.e., both with and without suicidal ideation), as one in ten people perceives a fully unmet mental health need and 4% perceives a partially unmet need [ 50 ]. Thus, those reporting suicidal ideation account for about one-quarter of all perceived unmet needs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, those reporting suicidal ideation account for about one-quarter of all perceived unmet needs. Prior research in the same sample found that a preference to solve problems on their own is the most important barrier for not seeking any care, and cost of services is the most important barrier for not seeking additional care among people with a common mental disorder [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, a third of those with suicidal ideation who did seek help thought the help was insu cient. It is unclear what exactly underlies this nding, but prior research in the same sample found that a preference to solve problems on their own is the most important barrier for not seeking any care, and cost of services is the most important barrier for not seeking additional care among people with a common mental disorder (30).…”
Section: Discussionmentioning
confidence: 99%
“…Although the importance of this statement is increasingly acknowledged, there are still several barriers to the effective delivery of mental health care. Common barriers include stigma and long waiting lists ( Corrigan, 2004 ; Rens et al, 2021 ), resulting in high unmet need, which can be defined as the failure to provide necessary care to individuals struggling with mental health problems ( Sherbourne et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%